2018
DOI: 10.1177/2047487318806359
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of LDL-cholesterol target value attainment differ in acute and chronic coronary heart disease patients: Results from DYSIS II Europe

Abstract: Background: Patients with coronary heart disease (CHD) and survivors of acute coronary syndrome (ACS) are at very high risk for adverse cardiovascular events. Lowering low-density lipoprotein cholesterol (LDL-C) can reduce the risk, with effective lipid-lowering therapy (LLT) readily available; however, dyslipidemia remains prevalent throughout Europe. Design: The observational Dyslipidemia International Study II (DYSIS II) aimed to identify unmet treatment needs in adult ACS and CHD patients. Data for the sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 31 publications
(43 reference statements)
3
39
1
Order By: Relevance
“…About 31%-49% or more of patients with hyperlipidemia do not achieve LDL-C goals with current lipid-lowering therapies [31,32], and more than half of patients stop statin treatment within 1 year of initiation [33]. Sixty percent of patients who discontinue statins report different symptoms of drug intolerance as the main reason for discontinuation [34].…”
Section: Plos Medicinementioning
confidence: 99%
“…About 31%-49% or more of patients with hyperlipidemia do not achieve LDL-C goals with current lipid-lowering therapies [31,32], and more than half of patients stop statin treatment within 1 year of initiation [33]. Sixty percent of patients who discontinue statins report different symptoms of drug intolerance as the main reason for discontinuation [34].…”
Section: Plos Medicinementioning
confidence: 99%
“…With the increase in age, ACS patients were less likely to reach LDL-C level < 70 mg/dl in our study, in contrast to previous reports. [ 32 33 34 ] Although the reason for this is not apparent, we did not reach any conclusion and suggested that additional studies are necessary to clarify these points specific to the Emirati population.…”
Section: Discussionmentioning
confidence: 69%
“…Two recent registry studies looked at the effectiveness of LDL-C control in populations with coronary artery disease (CAD). 15,16 In both of these registries approximately 42% of ACS patients had LDL-C levels below the 2016 ESC/EAS target of <1.8 mmol/l, but only 28% of those with stable CAD achieved this.…”
Section: Discussionmentioning
confidence: 99%